The Relationship between Cognitive Styles and English Productive Skills of Vocational High School Students in Makassar - Andi Nurfadillah Hamzah; Sultan Baa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The objectives of this research were (1) to find out the eleventh-grade students’ cognitive styles classification of SMK Telkom Makassar; (2) to find out the eleventh-grade students’ productive skills achievement of SMK Telkom Makassar; (3) to find out whether there is correlation between cognitive style and productive skills at the eleventh-grade students of SMK Telkom in the academic year of 2020/2021. The design of this research was correlational design. The total sample was chosen using quota sampling consisted of 30 tourism students in the eleventh grade at SMK Telkom Makassar in the academic year of 2020/2021. The instruments to collect the data were cognitive style test, speaking test and writing test. Group Embedded Figure Test (GEFT) was used to collect the cognitive style data while the speaking and writing test were used to collect the speaking and writing ability. In analyzing the data, the study used Person Product Moment formula to find the coefficient correlation and simple linear regression to find the significance and linearity of the variables. The findings indicated that (1) there were 16 Field Dependent (FD) students and 14 Field Independent (FI) students; (2) most of the students had poor achievement in speaking and writing test and there were a weak, positive correlation between students’ cognitive style and productive skills; (3) it was showed that the contribution of cognitive style to students’ speaking ability was 14.8%, and the contribution of cognitive style to students’ writing ability was 20.5%. Therefore, the study concluded that there was significant correlation between cognitive style and English productive skills of the eleventh grade students of SMK Telkom Makassar in the academic year of 2020/2021.